Representações sociais de idosos sobre o álcool e outras drogas - Moura, Samilla Gonçalves de (2019)
ABSTRACT Introduction: the consumption of alcohol and other drugs is a phenomenon that needs further investigation in the elderly population. Objectives: to analyze the social representations about alcoholism and other drugs built by the elderly people; to assess the risk use of alcohol and other drugs in the elderly. Method: this is an exploratory study with a qualitative approach, grounded on the theory of Social Representations, performed with 200 elderly citizens living in the towns of João Pessoa/PB and Cabedelo/PB. The research was approved by the Ethics Committee under opinion nº 2.190.153 and CAAE nº 67103917.6.0000.5188. In the Longstay Institutions and coexistence groups for the elderly people, we performed the interviews by applying the following instruments: Free Word Association Test, Short Michigan Alcoholism Screening Test-Geriatric Version and a sociodemographic form, which were treated by the IRaMuTeQ and SPSS softwares. Results: the elderly citizens were in average 70 years old; they were female, brown, Catholic, widowed; they could read and write; attended school for more than 6 years; were retired and received between 1 and 2 minimum wages; used the services of the Unified Health System. The institutionalized lived for less than 5 years and received weekly visits. The prevalence of alcoholism was 14%. The meaning of alcohol and other drugs was anchored in the negative attitude of the elderly person towards the harms to the individual, family and society. The following classes appeared: 1. Drugassociated violence; 2. Drug consequences; 3. Reasons for drug use; 4. Drugs and social exclusion. Final Considerations: we found that the use of alcohol and other drugs entails prejudices for the physical and psychological health, moral and social effects, such as family conflicts and expenses; increases the rates of traffic accidents, violence and premature deaths; besides provoking large social and economic repercussions. Health policies should cover the elderly population, since we have been observing the trends for increased use in this population.